Die Siegel der Erzbischöfe und Bischöfe in der Salzburger Metropole : Beschreibung, Abbildungen, Fotos und Zeichnungen - Höfer, Rudolf K.; Feiner, Martin (2021)
In historical sciences and in local history research, seal images of the bishops and archbishops of the dioceses in the Salzburg metropolis are repeatedly included. The photographic documentation of examples of all hitherto known seal typars documents for this first time the complete inventory of seals as an integral part of European cultural heritage. Drawings for numerous seals further facilitate access to these resources.